Salmon Fishing on the River - Branch Cultural Historical Association (2001)
There are many salmon holes on the River from the headwaters down to the Place. These include the Reefs, the Feeders, the Buckets, the Falls, the Strouters, Mortuary Place, Salmon Hole, Darby Bow, and Otter Rub. There are other favourite fishing pools further down along the Flats, and fishing is permitted in parts of the Gut. Branch River is also home to sea-run trout and it is common to see people trout off the wharves of the Gut and on Back of the Beach.